Pharmacokinetics, pharmacodynamics and safety profile of SKB336, a selective inhibitor of coagulation factor XI/XIa in healthy subjects - Xiang, Qian; Liu, Zhiyan; Xie, Qiufen; Zhao, Nan; Zhou, Shuang; Cao, Linyu; Zhao, Xia; Li, Yaling; Si, Jing; Wu, Qingmei; Ge, Junyou; Cui, Yimin (British journal of clinical pharmacology, 2025)
Coagulation factor XI (FXI) plays a crucial role in the intrinsic coagulation pathway, and inhibitors targeting it may mitigate the risk of haemorrhage compared to anticoagulants currently on the market. SKB336, a novel selective inhibitor of FXI/FXIa, has been shown to prolong the activated partial thromboplastin time (APTT) in both in vitro and in vivo studies. This study aimed to determine the safety, tolerability, pharmacokinetics and pharmacodynamics of SKB336 in healthy subjects. In this randomized, single-blinded, placebo-controlled and dose-escalation first-in-human phase I study, 60 healthy subjects were allocated to 6 cohorts (0.1, 0.3, 0.6, 1.25, 2.5 and 4 mg/kg) and received a single subcutaneous injection of SKB336 or placebo in a 4:1 ratio. The safety, tolerability, pharmacokinetics and immunogenicity were measured up to 85 days postdose. Exploratory analysis consisted of FXI activity and APTT. SKB336 was well tolerated in all 6 cohorts, without any haemorrhagic events, reported deaths or serious adverse events. No significant dose-dependent correlation was observed with the incidence of adverse events. Dose-dependent increases in the maximum observed drug concentration and area under the plasma concentration-time curve were observed. The mean elimination half-life was 21.3-33.5 days, indicating a potential monthly dosing frequency. The maximum inhibition rate of FXI activity for all 6 cohorts reached 0, 17, 28, 48, 54 and 59%, respectively. The maximum APTT ratio to baseline reached 1.09-, 1.26-, 1.47-, 1.77, 1.91- and 2.00-fold, respectively. SKB336 was generally tolerated, without any bleeding events in healthy volunteers. Besides, SKB336 presented a persistent dose-dependent prolongation of APTT and duration of FXI inhibition.